Pemanfaatan Audit Manajemen Pada Perusahaan - Meisya, Meisya; Arisman, Anton (Universitas Multi Data Palembang, 2024)
This research aims to determine the implementation of marketing function management audits, effectively, efficiently, economically. The type of research used is a qualitative approach. The subject of this research is the housing company PT Sukses Wijaya Adikarya. Data collection techniques use interviews (documentation) and interviews. The analytical method used in this research is qualitative descriptive analysis. The results of this research indicate that the management of the marketing function at PT Sukses Wijaya Adikarya Palembang is economical in managing the company's marketing costs and is quite effective and efficient for the marketing audit program at PT Sukses Wijaya Adikarya.